Pembuatan Animasi 2D Sebagai Media Promosi Wisata Goa Batu Hapu dengan Teknik Motion Graphic Menggunakan Metode MDLC: Making 2D Animation as a Tourism Promotion Media for Batu Hapu Cave using Motion Graphic Techniques Using the MDLC Method - Risdayati, Sunni; Sofyar, Sofyar; Mustaqimah, Umi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
In the province of South Kalimantan, there is an amazing tourist destination called Batu Hapu Cave, a cave formed by thousands of years of natural processes, decorated with stalactites and stunning rock formations. Apart from its beauty, this cave also has interesting historical and legendary value. However, promotional efforts carried out by the government and local communities through websites and oral stories are still less effective. Therefore, the author designed 2D animation using Motion Graphic techniques as a more attractive and effective promotional media. By utilizing the Multimedia Development Life Cycle (MDLC) method, this animation went through several phases, including conceptualization, design, material collection, assembly, testing and distribution. The animation was created using Adobe Illustrator and Adobe After Effects, and using SPSS to determine the results of the animated video. The results of tourist satisfaction with the resulting video reached 86.31%. This shows that the use of 2D animation with motion graphic techniques is effective in attracting the public and increasing tourist interest in Batu Hapu Cave. What must be paid attention to in a promotional video is the promotional message, visual details and animated movements.